2010
DOI: 10.1155/2010/269537
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Energy Absorbing TRIP-Steel/Mg-PSZ Composite: Honeycomb Structures Fabricated by a New Extrusion Powder Technology

Abstract: Lightweight linear cellular composite materials on basis of austenite stainless TRIP-(TRansformation Induced Plasticity-) steel as matrix with reinforcements of MgO partially stabilized zirconia (Mg-PSZ) are described. Two-dimensional cellular materials for structural applications are conventionally produced by sheet expansion or corrugation processes. The presented composites are fabricated by a modified ceramic extrusion powder technology. Characterization of the microstructure in as-received and deformed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Metal [248,249], reinforced plastic, Nomex paper and composite or hybrid materials [24,250] are the common materials used in making these honeycombs by sandwich construction acted as the basic supporting structure due to its high strength and low density.…”
Section: Functional Honeycomb Coresmentioning
confidence: 99%
“…Metal [248,249], reinforced plastic, Nomex paper and composite or hybrid materials [24,250] are the common materials used in making these honeycombs by sandwich construction acted as the basic supporting structure due to its high strength and low density.…”
Section: Functional Honeycomb Coresmentioning
confidence: 99%
“…The use of a metal as matrix material that is reinforced by Mg‐PSZ is quite new, especially in the combination of the austenitic steel showing the transformation induced plasticity (TRIP) effect with the MgO partially stabilized zirconia (Mg‐PSZ) 3–5. In contrast to the poor mechanical properties of the hot pressed composites of Guo et al 4, which showed no plasticity and failed in brittle behaviour, several reports have been published in the last two years that are focussed on this kind of the metal‐matrix composites (MMCs) 6–10. Several TRIP‐steel composites with different content of reinforcing ZrO 2 have been tested and are published elsewhere 9.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study was performed by Feng et al [37] including the theoretical method and the finite element analysis for predicting mechanical properties of BCC structures and uniaxialreinforced BCCZ and f2BCC structures manufactured by using the SLM technology. Martin et al [38] used a modified ceramic extrusion powder technology and analyzed mechanical properties and energy absorption efficiency of the honeycomb design based on austenitic stainless TRIP-steel and TRIP-steel/zirconia composite (TRIP-MC) materials.…”
Section: Introductionmentioning
confidence: 99%